Metastatic Ureteral Involvement of Non-Small Cell Lung Cancer - Koichi Kodama; Tetsuya Imao; Kazuto Komatsu (Case Reports in Medicine)
Metastases from a variety of malignant tumors can involve the ureters, but ureteral involvement by lung cancer is extremely rare and usually described at autopsy. We report a rare case of a 76-year-old man who presented with a three-month history of right flank dullness and was noted to have a nonhomogeneous retroperitoneal mass with hydronephrosis of the right kidney on computed tomography of the abdomen. Computed tomography of the thorax showed a nodule in the lower lobe, measuring 3×2 cm, in the right lung. After excluding the presence of other primary tumors and metastases, we reached a final diagnosis of solitary retroperitoneal metastasis of adenocarcinoma of the lung. Although rare, in patients of non-small cell lung cancer, presence of hydronephrosis should alert the physician to the possibility of metastasis.